Politik Hukum Pengampunan Pajak Terhadap Putusan Mahkamah Konstitusi - Anwar, Khoirul (Widya Yuridika, 2025)
Law Number 11 of 2016 concerning Tax Amnesty is a regulation from the government as part of increasing tax revenue in Indonesia. Tax amnesty is considered to have various shortcomings that harm the values of justice and constitutionality. Reviewing laws that have been decided by the Constitutional Court with Decisions Numbers 57, 58, 59 AND 63/PUU-XIV/2016 and strengthening the a quo law to remain valid in Indonesia. This decision is considered to be inconsistent with the social and legal facts that occur in society. The aim of this research is to answer and analyze how the Constitutional Court considered the review of the Tax Amnesty Law and to analyze the legal implications following the Constitutional Court's decision. The research method used in this research is normative legal research which is intended to examine legal politics and the implications of tax amnesty in Indonesia. The results and discussion in this research are to explain and analyze legal regulations as regulations made by the Indonesian government, and the Constitutional Court's consideration of requests for judicial review, which are linked to the legal implications of tax amnesty following the Constitutional Court's decision. Decisions Numbers 57, 58, 59 AND 63/PUU-XIV/2016 are the basis for the current implementation of tax amnesty and will become a reference in the future. The conclusion in this research is that the Constitutional Court stated that law number 11 of 2016 concerning Tax Amnesty does not conflict with the 1945 Constitution of the Republic of Indonesia. The success of this law is not perfect, because there is one element of tax amnesty acceptance, namely asset declaration, increase Tax and repatriation databases which have an impact on increasing new tax subjects and objects are not fulfilled.